Kajian Pendapat Komunitas Tentang Video Yang Berjudul Banyak Yang Salfok Tentang Kandang Ayam Kami - Tina Kartina; Nanang Trenggono; Nina Yudha Aryanti (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
Social interaction through social media, including social media usage, has become a habit in today's digital society. People are connected to each other, including friends and family. Likewise, the Instagram community bu_utig engages in discussions within a single social media space, @bu_utig. The purpose of this research is to describe a community opinion survey on a video titled "Many people are distracted by our chicken coop." The Instagram account @bu_utiq belongs to Mrs. Sri Hastuti, an entrepreneur and housewife living in Berbah District, Sleman Regency, Yogyakarta Province. Before her videos inspired many people, Mrs. Sri Hastuti had been actively sharing content on Instagram since May 2020. The research method used a qualitative approach with the concept of communication netnography. The concept of communication netnography is the study of online communities. The results of the study are videos that inspire, educate, and also include commercial activities such as question and answer activities for buying and selling through the concept of Computer-Mediated Communication (CMC). It explains that the community communicates through social media and presents new understanding through videos as a learning medium for building clean, neat, attractive, and impressive chicken coops. Chicken farming inspires others to visit the chicken farm and even buy chickens, thus influencing their behavior. Using the Cognitive Theory of Multimedia Learning, people learn through videos watched on social media and gain new knowledge through discussions and videos that can be replayed repeatedly as part of the learning process.